Internal iliac artery balloon occlusion in the management of placenta accreta: A systematic review and meta-analysis. Issue 139 (June 2021) - Liang, Deku; Zhao, Hu; Liu, Dandan; Lin, Yonghong
Highlights: No significant differences between the two groups in blood loss. No significant differences between the two groups in red blood cells transfused. Hysterectomy rates were not reduced by internal iliac artery balloon occlusion. Internal iliac artery balloon occlusion did not improve neonatal outcomes. Abstract: Purpose: To examine the effectiveness and safety of prophylactic internal iliac artery balloon occlusion for hemorrhage control in placenta accreta. Method: EMBASE, PubMed, and the Cochrane Central Register of Controlled Trials data-bases were searched through November 2020. Clinical trials comparing the management of placenta accreta with and without internal iliac artery balloon occlusion were included. The meta-analysis results were expressed as the risk ratio (RR) or mean difference, with 95 % CIs. Results: Fifteen studies including 1098 women were eligible. No statistically significant difference was found between the internal arterial balloon occlusion group and the control group with respect to estimated blood loss volume (–0.525 mL, [95 % CI, –1.112 to –0.061], p = 0.079.), red blood cells (RBCs) transfused in observational studies (-0.682 mL, [95 % CI, –1.540 to 0.176], p = 0.119.) and in randomized controlled trials (0.134 mL, [95 % CI, –0.214 to 0.482], p = 0.451.), intensive care unit admission (p = 0.197), hysterectomy in observational studies (p = 0.969) and in randomized controlled trials (p = 0.323), urinary system injury in observational studies (p = 0.182) and in randomized controlled trials (p = 0.956), Apgar score at 5 min (p = 0.641), and neonatal intensive care unit admission (p = 0.973). Conclusions: The currently available data demonstrate no significant differences between the internal iliac artery balloon occlusion group and the control group in blood loss and packed RBCs transfused for women with placenta accreta. Further large randomized controlled studies are needed to confirm our findings.